PROBLEMATIKA KONFLIK LIMA DESA ANTARA KABUPATEN KAMPAR DENGAN KABUPATEN ROKAN HULU TERHADAP PELAYANAN PUBLIK TAHUN 2010-2013 - Husein, Muhammad; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Five conflict between Kampar Regency Village with Rokan Hulu. Five villages in the territory of the conflict of two districts namely Desa Tanah Datar, Rimba Jaya, Rimba Makmur, and Intan Intan Jaya Muara. The result is uncertainty in the public service to the five villages. This conflict is of course the disadvantaged communities in the five villages, especially the issue of service, level of service both village and district level. During the five people in the village of confusion for siding with anyone for fear of cause horizontal conflict. The same confusion occurs when society requires administrative services, such as KTP, KK or other license, will be dealt to a confused society where the government, and this has gone on long enough without any clarity and firmness of both parties to the dispute this.The purpose of this study was to analyze diadakannnya conflict Prproblematika five villages on the quality of public services 2010-2013. Theory (approach) is used as an analytical tool in this study is the conflict theory and the theory of service. While the methods used in this research is descriptive qualitative research that is intended to provide a systematic overview of the observed phenomena.Based on these results, the problem of service as a result of the conflict has resulted in a five villages: First Flow Confusing service. For example, in the village of Intan Jaya which has double the Village Office, Village Office is representative of the Rokan Hulu and another one is a representative of the Office of Rural Kampar bad service flow is confusing people. Second, Service Being Ineffective. Where errors occur often fatal and can be detrimental to the local community, this is dictated by Riswoyo, one of the villagers of Intan Jaya when taking care of families and ID cards in the Head Office Kunto Darussalam. Third, Inequality Services. The existence of this conflict also resulted in five villages become uneven service reaching all the people residing in five villages in the conflict zone. There is a kind of grouping in five villages among residents who support one district. Fourth, Length of Time and Cost Issues Services. It starts with the process of service that can be said is contrary to the existing service procedures.Keywords: Conflict Five Villages, Kampar, Rokan Hulu, Services